Economic Development in Africa Report 2022 - United Nations Conference on Trade; Development (United Nations, 2022)
The report examines how African countries can work towards diversifying their exports by identifying feasible and innovative mechanisms for investment and trade policies to drive incentives to divert economic activities into transformative sectors. It aims to equip African governments and development partners with knowledge on how to diversify exports and promote structural transformation through the services sector, financial services, and private businesses, underpinned by capable, inclusive, and accountable institutions at the national, regional, and global levels.